Health-Care-Associated Infections Management, sow the seed of good habits: a grounded theory study - Taffurelli, Chiara; Cervantes Camacho, Victoria; Adriano, Giulia; Brazzioli, Cristina; Clemente, Stefano; Corda, Matilde; De Mari, Rita; Grasso, Viviana; Juranty, Beata; Sarli, Leopoldo; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: The reasons that condition and motivate adherence to good practices have a multifactorial nature. From the literature review, emerged different elements that interact within the operating context and represent a part of the variables that condition the “Best Practice”. The aim of this research was to investigate the variables that influence adherence to operators’ good practices. Methods: A qualitative study with Grounded Theory (GT) methodology was carried out, which leads to the establishment of a theory about basic social processes. This theory is based on the observation and perception of the social scene and evolves during data collection. Data collection took place through interviews with the participants, through an ad hoc semi-structured interview grid. The initial sampling consisted of 12 health workers, while the theoretical sample was made up of 6 health workers. Results: The analysis organization through the creation of schemes and diagrams has allowed to formulate different concepts including: false beliefs, knowledge and emotions experienced, that connect with the initial condition of Unconsciousness unaware; awareness of the consequences, team, welcome the new, which are connected to the intermediate phase of Revolution of the professional oneself; awareness of the limits, culture, responsibility, context, rigor and control that connects to the final state of Attentive Habit. Conclusions: The theoretical model develops through a path of growth and revolution that starts from the roots of an Unconsciousness unaware and brings with it the seed of a model.